Last active
October 12, 2017 15:37
-
-
Save petered/e86de1a6fd8422f68f09984ab8f82e66 to your computer and use it in GitHub Desktop.
2017-10-12 Kasper
This file contains hidden or bidirectional Unicode text that may be interpreted or compiled differently than what appears below. To review, open the file in an editor that reveals hidden Unicode characters.
Learn more about bidirectional Unicode characters
# 1) Simple Maximum Likelihood | |
F --> X | |
$$ | |
p(F=1 | X=x) = \frac{p(X=x|F=1) p(F=1)}{p(X=x)} = \frac{p(X=x|F=1) p(F=1)}{p(X=x|F=0)p(F=0) + p(X=x|F=1)p(F=1)} | |
$$ | |
Now, you've learned $p(F)$ and $p(X|F)$ over the dataset, so we can solve for this. | |
# 2) C causes X and F: p(X, F | C) = p(X|C) p(F|C) | |
C --> F | |
'---> X | |
Train naive-bayes EM by just concatenating F onto X, then marginalizing out C at test time. Then in your EM model, you've trained $p(F|C)$, $p(C)$, $p(X|C)$. And you can infer: | |
\begin{align} | |
p(F|X) &= \sum_{c\in |C|} p(F, C| X) \\ | |
&= \sum_C p(F, C, X)/p(X) \\ | |
&= \sum_C p(F|C) p(X|C)p(C) /p(X) \text{... Because of the graph structure}\\ | |
&= \sum_C p(F|C) p(C|X) \text{... Bayes rule}\\ | |
&= \frac{\sum_C p(F|C) p(X|C)p(C)}{\sum_{C}p(X|C)p(C) } | |
\end{align} | |
**Using past customer data**. | |
In your "averaging" assumption, you average out the latent distributions of transactions for a given customer. | |
\begin{align} | |
\hat p(C|X=x) &= \frac1N \sum_{x': x'_{id}=x_{id}} p(C|X=x') \\ | |
&= \frac1N \sum_{x': x'_{id}=x_{id}} \frac{p(X=x'|C)p(C)}{P(X=x')}\\ | |
&= \frac1N \sum_{x': x'_{id}=x_{id}} \frac{p(X=x'|C)p(C)}{\sum_C(X=x'|C)p(C)}\\ | |
\end{align} | |
So you could plug this in to the above equation: | |
\begin{align} | |
p(F=1|X=x) &= \sum_{c\in |C|} p(F=1|C=c)\hat p(C=c|X=x) | |
\end{align} | |
#3) F and C cause X | |
C --> X <-- F | |
You need to define $p(X|C,F)$ now, which we discussed before. | |
I think | |
$$ | |
$$ | |
... TODO: Fill in. |
Sign up for free
to join this conversation on GitHub.
Already have an account?
Sign in to comment